MANAJEMEN PRODUKSI PADA PEMBUATAN OMNIBUS MUSIC VIDEO BIN IDRIS DI EPI PRODUCTION - Anak Agung Ngurah Narendra Prema P; Nyoman Lia Susanthi; Ida Bagus Hari Kayana Putra (CALACCITRA: JURNAL FILM DAN TELEVISI, 2023)
The music video is a type of audio-visual work that is created in the form of a collection of videos that can represent the lyrics of a song. It Made to tell the audience how the song is visualized and can be enjoyed by the eyes of the audience. The producer is a very important role and must be present in an audio-visual production. The producer's job is to manage the production so that it can be well prepared, runs smoothly, and finishes on time starting from the pre-production to the post-production stage to carry out the promotion and distribution of works. The production of an omnibus music video work at EPI Production is a final project work produced with a musician named Bin Idris. Bin Idris is the name chosen by Haikal Azizi to carry out his solo project as an independent musician since 2016. The production management was applied to the creation of Bin Idris' omnibus music video at EPI Production. This activity was implemented to implement the concepts, stages, and authenticity of this omnibus music video production management. Besides that, it can compile seven draft management concepts for Bin Idris' music video production. Using the themes of mind, body-soul, and spirit in its planning, it produces three music video works with an omnibus concept that correlates with one music video and another. The application of production management in this omnibus work is applied based on the shooting location. As for the several locations used, you can shoot twice for different music videos. This is done in an effort to increase efficiency and prevent production costs from being incurred again. Through the omnibus concept which is usually produced with the concept of short or feature films, the writer and the entire production team apply this work to the music video concept so that it is hoped that it can create a new authenticity in the work that has been produced.